Methods and Sequelae of Torture: a study in Sri Lanka - De Zoysa, P.; Fernando, R. (My University, 2007)
A retrospective study was performed to document the physical and psychological methods of torture and their sequelae on 90 victims of torture who attended the Family Rehabilitation Centres in Vavuniya, Trincomalee and Anuradhapura, using a standard assessment format. The study showed that the methods of torture practised in Sri Lanka are similar to that of other countries. The methods are physical and psychological. Being a victim of a traumatic event would be physically and psychologically stressful.